IMPACTS OF LABOUR SHORTAGE ON ORGANIZATION PERFORMANCE: A CASE STUDY MINISTRY OF WATER AND IRRIGATION-TANZANIA - James Kalimanzila Matemani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
Labour shortage is the most challenging factor in economic growth in Tanzania particularly in Water and Health sectors. The Ministry of Water currently is facing critical labour shortage particularly technical staffs and engineers in both rural and urban water Offices. This problem have caused by many factors including, lack of promotion, lack of motivation, job mishmash, and low salary. This paper analysis and demonstrated recognition and good working environment as the key players in retaining labour and removing labour shortage in an organization. Many scholars demonstrates low salary and promotion as the only key players and forget about good working environment and recognition. The objective of this study is to investigate the scope and impacts of labour shortage on organizational performance. Likewise, the study have more significant in reminding the organization about the values of Human Resources for its development. In analyzing the study problem in this study conceptual and theoretical framework have been used. The study have used both qualitative and quantitative method in collecting and analyzing data obtained from different sources. Likewise this study have used hypothesis and theories to describe the results. The results of this finding is described through figures percentages and statistics chats which shows the importance and significant of promotion and good working environment in employees retention. All in all Tanzania suffers from considerable human resources constraints including inadequate staffing, imbalances in deployment and retention of professional water technical experts and supporting staffs, hence poor service delivery and economic stagnation, here the government must create good policies and proper environments to the workers.